Comparisons of electrophysiological characteristics, pacing parameters and mid- to long-term effects in right ventricular septal pacing, right ventricular apical pacing and left bundle branch area pacing - Wenhua Li; Yu Ding; Chao Gong; Genqing Zhou; Xiaofeng Lu; Yong Wei; Shi Peng; Lidong Cai; Tianyou Yuan; Fangfang Li; Shaowen Liu; Songwen Chen (BMC Cardiovascular Disorders, 2022)
Abstract Background As a near-physiological pacing innovation, left bundle branch area pacing (LBBAP) has drawn much attention recently. This study was aimed to investigate the electrophysiological characteristics, unipolar/bipolar pacing parameters and mid- to long-term effects and safety of three different pacing methods and identify possible predictors of adverse left ventricular remodeling. Methods Ninety-two patients were divided into the LBBAP group, right ventricular septal pacing (RVSP) group and right ventricular apical pacing (RVAP) group. Baseline information, electrophysiological, pacing and echocardiographic parameters were collected. Results The three pacing methods were performed with a similar high success rate. The paced QRSd was significantly different among the LBBAP, RVSP and RVAP groups (105.93 ± 15.85 ms vs. 143.63 ± 14.71 ms vs. 155.39 ± 14.17 ms, p < 0.01). The stimulus to left ventricular activation time (Sti-LVAT) was the shortest in the LBBAP group, followed by the RVSP and RVAP groups (72.80 ± 12.07 ms vs. 86.29 ± 8.71 ms vs. 94.14 ± 10.14 ms, p < 0.001). LBBAP had a significantly lower tip impedance during the procedure and 3-month follow up as compared to RVSP and RVAP (p < 0.001). Higher bipolar captured thresholds were observed in LBBAP during the procedure (p < 0.001). Compared to the baseline values, there was a greater reduction in left ventricular end-diastolic dimension (LVEDD) in the LBBAP group (p = 0.046) and a significant enlargement in LVEDD in the RVAP group (p = 0.008). Multiple regression analysis revealed that the Sti-LVAT was a significant predictor of LVEDD at 12 months post-procedure. At the 24-h post-procedure, significant elevations were observed in the cTnI levels in LBBAP (p < 0.001) and RVSP (p < 0.05). More transient RBB injury was observed in LBBAP. But no significant difference was found in cardiac composite endpoints among three groups (p > 0.05). Conclusions LBBAP demonstrated a stable captured threshold, a low tip impedance and a high R-wave amplitude during the 12-month follow-up. Left ventricular remodeling was improved at 12 months post-procedure through LBBAP. The Sti-LVAT was a significant predictor of left ventricular remodeling. LBBAP demonstrated its feasibility, effectiveness, safety and some beneficial electrophysiological characteristics during this mid- to long-term follow-up, which should be confirmed by further studies.